COVID 19 and myoclonus, do hemodialysis patients have more risk? - Salia Virxinia Pol Heres; Nuria Aresté Fosalba; Ana Barragán-Prieto; Wenceslao Adrián Aguilera Morales; Mercedes Salgueira (Nefrología (English Edition), 2024)
We discuss two recent cases from our hospital in which two patients with ESKD receiving periodical hemodialysis (HD) and SarS-Cov-2 infection suffered movement disorders, being the onset related to the HD sessions in both. First case is a 78 year-old woman who is admitted with generalized myoclonic status epilepticus and second case is a 46 year-old male who starts repeatedly suffering myoclonus during his hemodialysis sessions on day +10 after testing positive (asymptomatic infection). There are two main hypotheses when it comes to myoclonus and CNS disorders in COVID19, post-hypoxic origin and inmunomediated postinfectious origin. We wonder if they could both be interacting in patients with kidney disease, and especially in those who receive hemodialysis, maximizing the risk of suffering this type of disorders. Resumen: Presentamos dos casos de pacientes con enfermedad renal crónica G5D en programa de tratamiento renal sustitutivo (TRS) con hemodiálisis (HD) periódica e infección por SARS-CoV-2 que sufrieron trastornos del movimiento cuya aparición coincidió cronológicamente con las sesiones de hemodiálisis. El primero es una mujer de 78 años que en el día +5 de síntomas sufrió un status epiléptico mioclónico generalizado; y el segundo un varón de 46 años que en el día +10 de positividad comenzó a experimentar durante las sesiones de hemodiálisis episodios de mioclonías en miembros superiores. Las dos hipótesis con mayor fuerza para explicar la aparición de mioclonías y trastornos del sistema nerviosos central (SNC) en la enfermedad COVID-19 actualmente son el origen posthipóxico y el origen postinfeccioso inmunomediado. Es posible que la interacción entre ambos factores en pacientes con enfermedad renal, y especialmente en hemodiálisis, potencie el riesgo de sufrir estas alteraciones.